Problematika Pelaksanaan Pendidikan Kewirausahaan Pada SMK Attaqwa Kabupaten Bekasi - Widya Nuriyanti; Aster Pujaning Ati (Jurnal Ilmiah Wahana Pendidikan, 2020)
The purpose of this study is to describe the problems of implementing entrepreneurship education at SMK Attaqwa Bekasi Regency and describe what efforts are being made to overcome the problems faced. The type of research used is qualitative research, researchers collect data and conduct observations, interviews and documentation. The collected data were analyzed using descriptive analysis. The results showed that the interest in learning entrepreneurship was lacking. Meanwhile, the efforts that have been made by schools and teachers include the addition of facilities and infrastructure, the use of various learning media, additional business capital, and additional training. This has been shared with the Pihka foundation and the principal, and at the same time the researchers provide suggestions for what they can take.